Renewed Thinking on Strategic Governance of University:A Review - Bhushi, Umesh M.; Vizayakumar, K.; Dandagi, S. B. (Journal of Engineering Education Transformations, 2010)
Universities are in the knowledge business, and are involved in knowledge creation, dissemination, and learning. Universities do perform multiple roles, like creating new knowledge, acquiring new capabilities and producing an intelligent human resource pool. The University’s mission should endeavor towards providing education of the highest quality coupled with a leading contribution to the advancement of knowledge, thereby developing in students the imagination, talents, creativity and skills necessary for the varied and rapidly changing requirements of modern life. The pace and growth of Modern Science and Technology is so rapid that the Technical Know-how and its applications are vital for the nation s economic advancement. Engineering is one such profession that affects all aspects of modern life. The education of an engineer is demanding; it not only benefits humanity but also provides great rewards for the future and personal satisfaction from pursuing such a career. Five significant contributions of the university to the nation are: educating the citizens and leaders who think critically and independently; to model freedom of expression and freedom of inquiry; to serve as an engine of economic growth and prosperity; to foster the development of the community that surrounds; and to promote greater understanding among the peoples and nations of the world. How does the perspectives of university, its junctions, role differ across the countries based on the need, is it feasible to have an integrated cross cultural analysis to arrive at an integrated approach, this needs a perspective study across the countries. The paper provides a birds eye view oj these differing perspectives as a precursor need for setting lip of Technical University and its effective governance.